Using agile methodologies for adopting COBIT - Amorim, A. C.; Silva, M. M. Da; Pereira, R.; Gonçalves, M. (Information Systems, 2021)
COBIT 5 is a widely-used framework for implementing sound governance of enterprise IT (GEIT). Currently, the ISACA's official implementation solution follows a sequentially ordered process, raising several issues related with lack of commitment from top management and misaligned solutions. Nevertheless, new project life-cycle strategies have emerged along with the agile paradigm for project management, providing flexible and adaptable environments for projects where the solution is complex and not clear, delivering the product incrementally with feedback loops. This research aims to eliminate some known challenges of COBIT 5 adoptions by providing a Scrum based methodology to address these programmes. Design Science Research Methodology was used to guide this work, where two iterations on the solution development, demonstration and evaluation activities were performed. With two different iterations to the same solution and two distinct demonstrations, it was possible to identify several relevant findings. Overall, the results demonstrated that an agile methodology is not sufficient to reduce the resistance to changes, however, it increased the commitment from senior managers on the adoption of new practices and allowed to detect scope misalignment earlier in the development of solutions.